Pulsation Characteristics of Jovian Infrared Northern Aurora Observed by the Subaru IRCS with Adaptive Optics. Issue 21 (5th November 2018) - Watanabe, H.; Kita, H.; Tao, C.; Kagitani, M.; Sakanoi, T.; Kasaba, Y.
Abstract: We report narrow band‐filtered imaging observations of the Jovian H3 + 3.4‐μm emission using the IRCS (infrared camera and spectrograph) on the Subaru telescope taken on 25 May 2016. Approximately 1 hr of data was taken at intervals of 45–110 s, with high spatial resolution ( 0.2 arcsec) using adaptive optics. In the northern polar region, we found bright patch‐like emissions on the poleward side of the main oval. One of them had a pulsation period of 10 min. We utilized an H3 + emission model to investigate the response time of the H3 + emission to abrupt and periodic variations of the precipitating electron flux. The model showed that the H3 + emission could pulsate with this timescale due to a modulated flux of the precipitating electrons in the kilo‐electron‐volt to tens of kilo‐electron‐volt energy range. Plain Language Summary: We made a movie of the Jovian infrared aurora for the first time. The high spatial resolution images were observed for 1 hr with the time interval of 45–110 s using the infrared camera of the Subaru‐8‐m telescope. This movie showed that the infrared aurora from the hydrogen ion molecule H3 + had patchy structures on the northern auroral region and a pulsation period of 10 min. Our model analysis proved that such a fast variation could be driven by the modulation of the kilo‐electron‐volt to tens of kilo‐electron‐volt electrons coming into Jupiter. Key Points: We took infrared images of the Jovian H3 + aurora for 1 hr at time intervals of 45–110 s with the assistance of adaptive optics The aurora images showed a patchy structure on the polar side of the northern main oval with a pulsating interval of 10 min A model analysis showed that such a fast variation can be driven by the modulated electron flux with energy in the kilo‐electron‐volt to tens of kilo‐electron‐volt range